Isolation, Amplification Approaches of Human Pokemon gene (ZBTB7) and Incorporation into Yeast Vector - Nawal Kadem Mohammed (Institute of Medico-legal Publications Pvt Ltd, 2020)
The transcription repressor protein ZBTB7 (FBI1, BTB-ZF protein LRF) known as a Pokemon is critical factor in oncogenesis which is encoded by ZBTB7 gene. ZBTB7 processes by controlling the pathways that are required to transform normal cell to cancerous one. It produces its effects by repressing the function of other proteins including a tumor suppressor protein ARF leading to lymphomas and other oncogenic effects and present in very high level in certain type of B cell. So the structural study of the translation product of this gene is an important task to know about the carcinoferous effect of ZBTB7 along with their interactive pattern with co-repressor which prone transcription repression by stopping the activity of transcription factors. In the present project DNA binding domain of ZBtB7 gene’s cDNA is developed and cloned into suitable yeast vector.